Calculation of the transmission function for remote sensing by meteorological satellite (extended abstract) - Ito, Seigo; Tanaka, Shinya; Yoshino, Takeo; Yamanouchi, Takashi; Kawaguchi, Sadao (国立極地研究所, 1982)
departmental bulletin paper